Dissolved, Transformed, Retained : Carbon Cycling in Freshwater and Coastal Systems - Jones, Kevin ; 0000-0001-8837-0986 (Lund University (Media-Tryck), 2025)
Freshwater ecosystems in boreal and temperate regions are undergoing rapid change as increasing inputs of terrestrially derived dissolved organic matter (DOM) and nutrient enrichment alter ecosystem functioning. These processes, known as brownification and eutrophication, vary across space and time but can profoundly reshape carbon cycling, microbial activity, and water quality. This thesis investigates how seasonal variability, nutrient availability, and wetland design interact to influence DOM transformations in freshwater and coastal systems. Field studies and experimental manipulations demonstrate that pulses of terrestrial DOM during high- flow events and seasonal transitions strongly affect DOM composition and microbial bioavailability. Nutrient enrichment stimulates microbial uptake but lowers bacterial growth efficiency, shifting carbon use toward respiration and CO₂ release rather than biomass production. Sunlight also plays a critical role: photochemical processes fragment aromatic DOM into smaller, more labile compounds, particularly in shallow, well-lit waters where exposure is prolonged. The relative importance of microbial versus photochemical pathways shifts with season, with warmer nutrient-rich periods amplifying microbial respiration and clearer shallow systems enhancing photodegradation. Constructed wetlands provide an opportunity to harness these processes for management. Results show that both water depth and seasonal light regimes determine whether DOM removal is dominated by microbial reworking or photochemical breakdown. Shallow wetlands promote rapid photodegradation, while deeper systems sustain microbial transformations that further process DOM before it leaves the wetland. Overall, this thesis demonstrates that the fate of DOM in freshwaters is shaped by the combined effects of light, nutrients, hydrology, and wetland design. By linking natural seasonal variability with targeted wetland manipulations, it provides new insights into how freshwater carbon cycling may respond to environmental change and highlights how strategically designed wetlands can mitigate brownification across seasons.
Keywords: Dissolved organic matter; brownification; eutrophication; aquatic biogeochemistry; microbial carbon cycling; photodegradation; constructed wetlands; seasonal variability